The best... and the rest. - Cairncross, Frances (Economist, 1999)
Focuses on the strike of Finnish dockers demanding wage hike. Information that Finnish dockers grievances was that Estonian dockers just across the Baltic, were paid only a quarter of their wages, putting Finnish jobs in jeopardy; Comment that Estonia's software programmers can sell their services abroad without leaving the country; Opinion that immigration officials may still bar the door to foreigners who want to apply in the flesh, but more and more services can be delivered online; Comment that companies see pay as their main tool for recruiting, motivating and retaining good people.